The Cruise of the Frolic - Kingston, William Henry Giles, 1814-1880 (Salt Lake City, UT : Project Gutenberg, 2010)
"The Cruise of the Frolic" by W.H.G. Kingston is a fictional narrative written in the mid-19th century. This seafaring adventure captures the experiences of a group of young people as they embark on nautical journeys aboard the yacht "Frolic," led by the exuberant Ned Hearty. The plot revolves around themes of romance, camaraderie, and the pleasures of yachting, alongside the excitement of social gatherings and regattas. The opening of the narrative sets the stage with the introduction of the main characters and the vibrant yachting culture of Cowes, particularly during regatta season. It begins with a preface suggesting that the adventures recounted are rooted in the author$1 (Bs experiences, while the first chapter presents a nostalgic look at the lively scene of a regatta filled with colorful boats and enthusiastic participants. We meet a variety of characters, including Miss Seaton, the belle of the group, and others preparing for a day on the water. The lively interactions aboard the "Frolic" are animated by playful banter and burgeoning romantic interests, hinting at future entanglements as the group embarks on their day of excitement on the waves. (This is an automatically generated summary.)s
Release date is 2010-11-29
Produced by Nick Hodson of London, England
Keywords: Conduct of life -- Juvenile fiction; Pirates -- Juvenile fiction; Yachts -- Juvenile fiction; Adventure and adventurers -- Juvenile fiction; Voyages and travels -- Juvenile fiction; Seafaring life -- Juvenile fiction; Natural history -- Juvenile fiction; Sailors -- Juvenile fiction; Youth -- Conduct of life -- Juvenile fiction; Courtship -- Juvenile fiction; Mediterranean Region -- Description and travel -- Juvenile fiction